Clinical Characteristics and Surgical Outcome of Patients with Pituitary Tumour: Our Experiences at a Tertiary Centre (Nepal Journal of Neuroscience, 2025)
Introduction: Pituitary tumours are a common heterogeneous group of lesions of the central nervous system. The overall prevalence of pituitary tumour in the general population is estimated to be 16.7%. Pituitary tumours present with a wide range of clinical spectrum. The standard of care for a pituitary tumour involves primary surgical intervention followed by radiotherapy/chemotherapy of the residual or recurrent tumour.Methodology: A retrospective study over a period of ten years (2013-2023 AD) of patients with pituitary tumour admitted to the Department of Neurosurgery was done. Pituitary tumour was confirmed by MRI brain with dynamic contrast whenever needed. Demographic profile of the patients, presenting complaints, radiological information about the tumour, intraoperative event, post-operative event were collected. The patients were followed up either in person or through telephone. All statistical analysis was done using SPSS software version 26.Results: Of the 104 patients identified in the study period, 15 patients were excluded due to incomplete data and conservative management. Of the 89 patients included, there were 43 male patients. The mean age of the population was 47.9 (±13.97) years. The majority of the patients (66.3%) had non-functioning pituitary tumour. Most of the patients (52.8%) were managed with transcranial approach. The majority of the patients showed improved outcome in terms of visual symptoms, acromegaly features and hormone profile at 3 months post-surgery follow up.Conclusion: Pituitary tumours are a heterogeneous group of lesions of the central nervous system presenting with a wide range of clinical spectrum. The management is primarily surgical with recent trend of surgical approach being endoscopic transnasal transsphenoidal.